Grouping of Scots Pine (Pinus sylvestris L.) Seed Stand Populations in Western Blacksea Region of Turkey by Seedling Morphological Distance - Ayan, Sezgin; Şevik, Hakan; Bilr, Nebi (Pak. Journal of Biological Sciences, 8 (11):1548–1552., 2005)
Nine populations of Scots pine, sampled from Western Blacksea Region: were grouped by seedling morphological distance and cluster analysis in this study. For that purpose, number of cotyledon, lengths of cotyledon, epycotyl and hypocotyl and height, root-collar diameter, number of branch, stem and root chy weights were measured on two-month old, and one-year old seedlings chosen randomly. The differences among the populations for the characteristics of one-year old seedlings were larger than two-months old seedlings. For instance, while epycotyl length varied between 11.9 and 15.3 mm (difference was 1 1 0): stem dry weight varied between 164.3 and 256.6 mg (56%) among populations. Morphological distance among populations between 0.297 and 5.288. In addition, populations were gathered two mam groups which are Ankara-Yenice, Kastamonu-Balliclag and Adapazari-Dokurcun and the others and three sub groups according to cluster analysis. Results of the study could be used in breeding and afforestation of the species such as preparation of gene maps, determination of breeding populations, gene conservation areas and seed sources.
Keywords: Pinus sylvestris, breeding, seed sources, penrose, cluster analysis, seedling morphology